Ayurvedic Approach in the Management of Dyslipidaemia (AYUSHDHARA, 2025)
Dyslipidaemia, commonly characterized by deranged serum lipids, corresponds to Medoroga (dyslipidaemia) in Ayurveda, a condition arising from Meda Dhatu Dushti (vitiated fat tissue) due to Kapha-Medo Vriddhi (increase of Kapha and Meda dhatu). This case study presents a 46-year-old male patient who complained of fatigue, breathlessness on exertion, excessive sweating, and disturbed sleep. Patient lifestyle included a sedentary routine, irregular food habits, and high intake of oily and processed foods. Initial lipid profile showed raised Triglycerides (288mg/dL) and VLDL (very low-density lipoprotein) (58mg/dL), indicating Rasa-Meda Dushti and impaired Agni. An Ayurvedic line of treatment focusing on Agnideepana (stimulation of digestive fire), Amapachana (digestion of toxins), Medohara (fat reducing) and Kapha-Vata shaman was initiated, comprising of classical formulations, dietary correction (Pathya-Apathya), and lifestyle modifications including regular exercise and stress management. After a treatment duration of 1-month, significant clinical improvement was observed Triglycerides dropped to 123mg/dL and VLDL (very low-density lipoprotein) to 25 mg/dL. The patient reported improved energy levels, better sleep quality, and reduced sweating. This case underlines the effectiveness of integrative, individualized Ayurvedic management in addressing dyslipidaemia holistically by correcting the root cause rather than just controlling serum lipid values.